ESTUDO QUÍMICO DO SOLO E LIXIVIADO DO ATERRO CONTROLADO DO BOTUQUARA - (:unkn) unknown (UNIVERSIDADE ESTADUAL DE PONTA GROSSA, 2008)
Currently, the production and storage of solid residues have generated a discuss range about linked aspects to the disease propagation and environment damage, mainly due to the formation of leach and its infiltration, could cause earth contamination, flow and ground water. The final disposition place of trash at Ponta Grossa city started out in 1969, in an appearance of garbage in a Botuquara’s region, became controlled garbage earthwork in 2001. The aim in this paper is evaluate the characteristics of same earth points and the leach of Botuquara’s controlled garbage earthwork, checking in this area possible trends of contamination. It were accomplishing analyses of pH, OM, organic carbon, total nitrogen, C:N relation, CEC, bases saturation, K+, phosphates and sand contents, clay and silt to the earth and pH, CO, DO, phosphates, K+ and nitrogen to lixiviate. It also was checking the concentration of Ag, Cr, Cd, Cu and Fe, Mn, Ni, Pb and Zn on lixiviate and biodegradable metals and pseudo-total to earth. In the result show that the leach has risen contents of Mn, Ni, Fe, Cr, Cd, Pb, Cu, and Zn, low concentration of OD and high burden of nutrients. Earth show high concentration of Cr, Pb, Cd and Ag biodegradable and Pb, Cu, Cd, and Ag pseudo-total. The colloids saturation of soil means that the garbage earthwork reached retention capacity maximum. Like the degradation is slow and there is a continuous liberation of components to the environment, its can reached deeper layers is incorporate on lixiviate. If the resultant mix reaches ground water, it’s able to change the characteristics and pledge its use, characterizing a contamination process.
Keywords: resíduos sólidos; espécies metálicas; solo; lixiviado; solid residues; species metallic; earth; lixiviate; CNPQ::CIENCIAS EXATAS E DA TERRA::QUIMICA